Mean-square asymptotic stability of solutions of systems of stochastic differential equations with random operators - Yurchenko, I. V.; Yasinskaya, L. I.; Yasinsky, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain conditions of asymptotic behavior of trivial solutions of systems of stochastic differential equations with random operators.